1988
DOI: 10.1111/j.1365-2621.1988.tb10203.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensory Properties and Headspace Volatiles of a Peanut Beverage Processed at Different Temperature and Time Conditions

Abstract: Differences in sensory qualities of a peanut beverage processed at 85", loo", and 121°C for 5, 15 and 25 min were determined using analysis of variance (ANOVA) techniques. Temperature significantly affected cooked flavor, raw and cooked odors, viscosity and color. Time had significant effects only on cooked flavor and color. Factor analysis was used to determine relationships among sensory qualities and gas chromatographic peaks of the headspace volatiles. Seven factors accounted for 91% of data variance. Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Differences in viscosity among the bottleprocessed beverages are attributed to increased unfolding and aggregation of protein molecules and formation of hydrophilic protein-lipid complexes as severity of thermal treatment was increased. Rubico et al (1988) also observed increases in viscosity when increased heat treatments were applied to beverages prepared from unroasted peanuts. Commercial whole milk, lowfat milk, chocolate low-fat milk and chocolate drink had viscosities of 2.0 -t 0.00, 2.0 t-0.00, 12.7 + 0.26 and 4.9 t: 0.06 cps, respectively.…”
Section: Viscositymentioning
confidence: 94%
See 1 more Smart Citation
“…Differences in viscosity among the bottleprocessed beverages are attributed to increased unfolding and aggregation of protein molecules and formation of hydrophilic protein-lipid complexes as severity of thermal treatment was increased. Rubico et al (1988) also observed increases in viscosity when increased heat treatments were applied to beverages prepared from unroasted peanuts. Commercial whole milk, lowfat milk, chocolate low-fat milk and chocolate drink had viscosities of 2.0 -t 0.00, 2.0 t-0.00, 12.7 + 0.26 and 4.9 t: 0.06 cps, respectively.…”
Section: Viscositymentioning
confidence: 94%
“…For example, bottle-processed beverages have stronger cooked and raw flavours than kettle-pasteurized beverages (Rubico et al, 1988;Galvez et al, 1990), whereas homogenizing after kettle-pasteurizing facilitates production of beverages with smoother mouthfeel (Priepke et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The milk-like product produced is then homogenized, sterilized in much the same way as fresh milk, and also supplemented with vitamins and minerals and is sometimes flavored. Details of these methods are given in the works of Barley (1951), (Jasper, 1973), Mitchell (1950), Chandrasekhara et al (1971), Schmidt et al Mendelsohn (1980), Rubico et al (1987Rubico et al ( , 1988, and Chan Lee and Larry R. , . According to Rao et al (1964), peanut milk combined with other milks can be spray dried, and the powder has longer shelf-life and can be readily reconstituted in water.…”
Section: Introductionmentioning
confidence: 98%
“…Soaking and grinding full-fat raw peanuts with water to get slurry, subject to filtration produce usually peanut milk (aqueous extract of peanut kernels, Arachis hypogea L.) Beuchat et al, 1978;Bucker et al, 1979;Rubico et al, 1987Rubico et al, , 1988Chan et al, 1991Chan et al, , 1992Shurpalekar et al, 1964;Chandrasekhara et al, 1964; and also by grinding unsoaked roasted peanuts, raw full-fat, or partially defatted peanuts to form freeflow flour to which water may later be added to make an emulsion. Another way is to use the peanut milk or peanut protein isolates to extend animal milk (toned milk).…”
Section: Introductionmentioning
confidence: 99%
“…El método se ha aplicado al análisis de volátiles de muestras tales como hierbas aromáticas (Chialva, 1983), cacahuetes (Sanders, 1989), bebidas (Rubico, 1988), salmuera (Montano, 1990), etc. Sin embargo, en la bibliografía de los últimos años se encuentra una mayor aplicación del método a aceites.…”
Section: Espacio De Cabeza Estáticounclassified